THE CONTENT OF MEDIA LITERACY AND ITS MAIN CATEGORIES - Ochilov Sherzod Jurakulovich (TADQIQOTLAR.UZ, 2024)
Annotation. This article describes the content of media, media education, media literacy, information literacy, visual literacy, media literacy. Students are provided with information about the content of media literacy, the necessity and importance of media literacy in society.